2014
DOI: 10.1089/thy.2013.0274
|View full text |Cite
|
Sign up to set email alerts
|

FOXE1 Association with Differentiated Thyroid Cancer and Its Progression

Abstract: Background: Single nucleotide polymorphisms (SNPs) near thyroid transcription factor genes (FOXE1 rs965513/NKX2-1 rs944289) have been shown to be associated with differentiated thyroid cancer (DTC) in Caucasoid populations. We investigated the role of those SNPs in German patients with DTC and also extended our analysis to tumor stages and lymphocytic infiltration of the tumors (ITL). Methods: Patients with DTC (n = 243; papillary, PTC; follicular, FTC) and healthy controls (HC; n = 270) were analyzed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…8 (4). The association between rs965513 and thyroid cancer risk has been independently confirmed in different populations (5)(6)(7)(8)(9)(10)(11). The association was also observed in familial PTC and in patients with radiation-induced PTC (12)(13)(14)(15).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…8 (4). The association between rs965513 and thyroid cancer risk has been independently confirmed in different populations (5)(6)(7)(8)(9)(10)(11). The association was also observed in familial PTC and in patients with radiation-induced PTC (12)(13)(14)(15).…”
mentioning
confidence: 71%
“…To assess SNPs across the 9q22 locus and to identify functional SNPs, as well as additional associated variants that may contribute to PTC predisposition, we performed targeted next-generation sequencing in a gene-poor region of about 167 kb [genomic coordinates chromosome 9: 100455000-100622000 (GRCh37/hg19)] on DNA from 22 patients with PTC, including 10 [AA], 6 [AG], and 6 [GG] genotypes of the lead SNP rs965513. The region contains both coding genes (XPA and FOXE1) that flank the lead SNP.…”
Section: Resultsmentioning
confidence: 99%
“…The association of rs965513 and rs944289 with PTC was analysed by Liyanarachchi et al in cohorts from Poland and the United States [2], with results that are in accordance with our study. The association of rs965513, rs1867277, rs944289, and rs1443434 with PTC has been confirmed in different populations in recent years [8][9][10][11][12][13][14][15][16][17]. Moreover, four meta-analyses concerning the roles of rs965513, rs1867277, and rs944289 in PTC have been published: the association of rs965513 has been confirmed among both Caucasians and Asians, rs1867277 SNP was ana-…”
Section: Discussionmentioning
confidence: 89%
“…At the same time, Landa et al demonstrated an association between PTC and another SNP located in the 5-untranslated region of the FOXE1 -rs1867277 [4]. However, to date, only a few studies have been performed to assess the association of these SNPs with some clinical features of PTC [5,8,9]. To our knowledge, no study has analysed the mutual interactions between identified SNPs and their association with patient--related factors, like gender and age at PTC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the genetic factors, FOXE1 plays an important role in the morphogenetic process which is regulated by both cell-autonomous and mesoderm-derived mechanisms acting in concert to promote growth and survival of progenitor cells [19,20]. In other studies, the FOXE1 variants were associated with the risk of DTC in some populations, including Spain, Belarusian, Portuguese, et al [7,11,21,22].…”
Section: Discussionmentioning
confidence: 96%